Can Welfare Conditionality Combat High School Dropout? - Øystein Hernæs; Simen Markussen; Knut Røed (Institute for the Study of Labor (IZA), 2016)
Based on administrative data, we analyze empirically the effects of stricter conditionality for social assistance receipt on welfare dependency and high school completion rates among Norwegian youths. Our evaluation strategy exploits a geographically differentiated implementation of conditionality. The causal effects are identified on the basis of larger-than-expected within-municipality changes in outcomes that not only coincide with the local timing of conditionality implementation, but do so in a way that correlates with individual ex ante predicted probabilities of becoming a social assistance claimant. We find that stricter conditionality significantly reduces welfare claims and increases high school completion rates.
Keywords: H55; I29; I38; J18; 330; social assistance; activation; conditionality; welfare reform; school dropout